The emerging links between immunosenescence in innate immune system and neurocryptococcosis - Soraci, Luca; Beccacece, Alessia; Princiotto, Maria; Villalta Savedra, Edlin; Gambuzza, Maria Elsa; Aguennouz, M’Hammed; Corsonello, Andrea; Luciani, Filippo; Muglia, Lucia; Filicetti, Elvira; Greco, Giada Ida; Volpentesta, Mara; et al. (Frontiers in Immunology, 2024)
Immunesenescence refers to the age-related progressive decline of immune function contributing to the increased susceptibility to infectious diseases in older people. Neurocryptococcosis, an infectious disease of central nervous system (CNS) caused by Cryptococcus neoformans (C. Neoformans) and C. gattii, has been observed with increased frequency in aged people, as result of the reactivation of a latent infection or community acquisition. These opportunistic microorganisms belonging to kingdom of fungi are capable of surviving and replicating within macrophages. Typically, cryptococcus is expelled by vomocytosis, a non-lytic expulsive mechanism also promoted by interferon (IFN)-I, or by cell lysis. However, whereas in a first phase cryptococcal vomocytosis leads to a latent asymptomatic infection confined to the lung, an enhancement in vomocytosis, promoted by IFN-I overproduction, can be deleterious, leading the fungus to reach the blood stream and invade the CNS. Cryptococcus may not be easy to diagnose in older individuals and, if not timely treated, could be potentially lethal. Therefore. this review aims to elucidate the putative causes of the increased incidence of cryptococcal CNS infection in older people discussing in depth the mechanisms of immunosenscence potentially able to predispose to neurocryptococcosis, laying the foundations for future research. A deepest understanding of this relationship could provide new ways to improve the prevention and recognition of neurocryptococcosis in aged frail people, in order to quickly manage pharmacological interventions and to adopt further preventive measures able to reduce the main risk factors.